2022
DOI: 10.1186/s13256-022-03263-4
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tumor lysis syndrome in adrenal adenocarcinoma: a case report and review of the literature

Abstract: Background Tumor lysis syndrome is an oncologic emergency that classically occurs following cancer therapy, although spontaneous tumor lysis syndrome can also occur in malignancies, albeit rarely. Spontaneous tumor lysis syndrome has previously been reported in some hematologic malignancies, but it rarely happens in solid tumors and seems to be associated with a higher mortality rate. This is the first case of adrenal adenocarcinoma that developed spontaneous tumor lysis syndrome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, patients under treatment for hematologic malignancies, mainly BL and ALL, are at the highest risk for developing TLS. 15 Based on existing literature, certain intrinsic tumorrelated factors have been associated with an increased risk of developing TLS, such as high tumor cell proliferation rate, significant tumor burden, tumor chemosensitivity, and increased LDH levels, which were all seen in our case. Furthermore, it has been suggested that certain conditions, including preexisting uremia or hyperuricemia, decreased urinary flow or acidic urine, dehydration, oliguria, anuria, and renal insufficiency or renal failure may predispose patients to develop TLS, which was also observed in our case.…”
Section: Discussionmentioning
confidence: 57%
“…However, patients under treatment for hematologic malignancies, mainly BL and ALL, are at the highest risk for developing TLS. 15 Based on existing literature, certain intrinsic tumorrelated factors have been associated with an increased risk of developing TLS, such as high tumor cell proliferation rate, significant tumor burden, tumor chemosensitivity, and increased LDH levels, which were all seen in our case. Furthermore, it has been suggested that certain conditions, including preexisting uremia or hyperuricemia, decreased urinary flow or acidic urine, dehydration, oliguria, anuria, and renal insufficiency or renal failure may predispose patients to develop TLS, which was also observed in our case.…”
Section: Discussionmentioning
confidence: 57%
“…Hypouricemic agents such as allopurinol and rasburicase can be helpful in lowering serum uric acid levels. If the above measures are not effective and the following conditions are met, hemodialysis will be indicated in a case with severe oliguria or anuria, persistent hyperkalemia, hyperphosphatemia induced symptomatic hypocalcemia, and calcium phosphate product ≥70 mg/dl 14 …”
Section: Discussionmentioning
confidence: 99%
“…The patient was initially suspected of having tuberculosis and treatment was started, but because he was not relieved, he was referred to another center for further investigation. Our literature review suggested that although STLS has a worse prognosis in some cases, due to the poor prognosis of TLS in malignancies, particularly STLS, it is essential to consider the fact that TLS can occur spontaneously and it is important to initiate immediate treatment as any suspicious symptoms are noticed 14 . Meanwhile, PCL is an aggressive malignancy, and the overall prognosis of PCL is very poor with a median survival of 7–11 months, with up to 28% dying within the first month after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations